Blocking Protein Phosphatase 1 [PP1] Prevents Loss of Tether Elasticity in Anaphase Crane-Fly Spermatocytes - Forer, Arthur; Adil, Aisha; Berns, Michael W. (Frontiers in Molecular Biosciences, 2021)
In normal anaphase cells, telomeres of each separating chromosome pair are connected by tethers. Tethers are elastic at the start of anaphase: arm fragments cut from anaphase chromosomes in early anaphase move telomere-to-telomere across the equator to the oppositely moving chromosome. Tethers become inelastic as the tethers become longer during anaphase. Calyculin A (CalA), an inhibitor of protein phosphatases 1 (PP1) and 2A (PP2A), causes chromosomes at the end of anaphase to move backward from their spindle poles towards and across the equator, telomeres leading the way in moving towards telomeres at the opposite spindle pole. The experiments described herein show that CalA causes tethers to remain elastic throughout anaphase and that elastic tethers pull the chromosomes backwards at the end of anaphase. In our experiments cutting the tethers causes backwards movement to stop; severing arms during the backwards movements causes the backwards movements to stop; severing arms before the chromosomes reach the poles causes subsequent backwards movement to not occur; cutting the telomere towards which a chromosome is moving backwards causes the backwards movements to stop; and comparison of arm fragment movements in control cells versus in CalA-treated cells indicates that CalA prevents tethers from becoming inelastic as they lengthen. Thus, elastic tethers pull the chromosomes backwards once the polewards forces on the kinetochores are reduced. Inhibitors of PP2A do not cause the backwards movements (Kite and Forer, 2020), so inhibition of PP1 causes the tethers to remain elastic.